Sistem Layanan Sirkulasi di Perpustakaan Jurusan PGSD FIP UNP Bukittinggi - Gampala, Hengky; Syahyuman, Syahyuman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This research aimed to (1) describe the circulation service activities, (2) explane the chalanges faced in circulation service at the library of elementary teacher education department, education Facultas in Belakang Balok Bukittinggi. Method of research was observasion and interview. The research result showed that this library apply open access sistem in circulation service and use the browne system in borriwing. The chalanges in implementary this system were(a) borrowing and return procers in the same desk,(b) the difficulty in return the book into the book shelf, and the overdue in returning. Keywords: circulation services; open access